Implementasi Proses Perencanaan Sektor Publik dalam Alokasi Dana Desa untuk Program Ketahanan Pangan: Studi Kasus pada BUMDes Sukowiryo, Kecamatan Jelbuk - Tantri Maehap Sari; Fatihatur Rizqiyah; Wulan Puspita Sari; Ruwanda Oktavia Andini; Tasya Nur Imaniyah; Prillinaya Yudhistira; Oryza Ardhiarisca (CV Muara Edukasi, 2025)
This study aims to analyze the implementation of the public sector planning process in allocating Village Funds for food security programs at BUMDes Sukowiryo, Jelbuk District, Jember Regency. The research focuses on how the village government and BUMDes plan, implement, and evaluate the use of Village Funds to effectively support community food security. This study employs a qualitative approach with data collected through interviews, observations, and documentation involving village officials and BUMDes administrators. The findings indicate that the planning process has referred to participatory, transparent, and accountable principles; however, its implementation still faces challenges such as limited capacity of village officials, suboptimal coordination, and uneven community participation. The food security program based on cattle farming has shown positive impacts on increasing household income and ensuring the availability of animal-based food in the village. Nevertheless, its sustainability largely depends on consistent coordination and strengthened governance. Based on stakeholder theory, the success of the program is determined by the active involvement of all stakeholders in the planning and evaluation process. Therefore, enhancing the capacity of village officials, improving transparency in reporting, and expanding community participation are key factors in achieving effective and sustainable Village Fund management for food security